Staying or Leaving? Analyzing the Rationality of Rural-Urban Migration Associated with Farm Income of Staying Households: A Case Study from Southern Ethiopia - Beneberu Assefa Wondimagegnhu (Advances in Agriculture)
The research aims at analyzing the effect of rural-urban migration and remittances on farm income of rural households supported by a case study conducted in Southern Ethiopia. Using two-step estimations to measure the effect of outmigration, migrant sending families have gained higher farm income. In this regard, rural outmigration has been found to be a survival and income diversification strategy in the study area.